If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 95 = -6(1 + -2m) + 5 95 = (1 * -6 + -2m * -6) + 5 95 = (-6 + 12m) + 5 Reorder the terms: 95 = -6 + 5 + 12m Combine like terms: -6 + 5 = -1 95 = -1 + 12m Solving 95 = -1 + 12m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-12m' to each side of the equation. 95 + -12m = -1 + 12m + -12m Combine like terms: 12m + -12m = 0 95 + -12m = -1 + 0 95 + -12m = -1 Add '-95' to each side of the equation. 95 + -95 + -12m = -1 + -95 Combine like terms: 95 + -95 = 0 0 + -12m = -1 + -95 -12m = -1 + -95 Combine like terms: -1 + -95 = -96 -12m = -96 Divide each side by '-12'. m = 8 Simplifying m = 8
| 41-2x=6-7x | | ln*x+ln(x+1)=ln*3+ln*4 | | X(9+1)=r | | 6.2n-5.2-8.6=-1.7 | | 41-2x=7-7x | | 0=4x^2+24x+6 | | 4x-2.5=13.9 | | 8y+9y=17y-5y | | g(x)=-3x^2+30x+33 | | d=p+fx | | 9n-9n= | | 6x=2z+12 | | 24=-4/5u | | x^2-3+40=0 | | -6x+5x=1 | | Fx=h | | -9+5x+1-7x=8-6x | | g(x)=4x^2-21x-18 | | .0627=x^2+.190x | | 9g-(-5)=-4 | | 2x+10-4x+2=8 | | 2x+80=3x | | 3+3x=-3+x | | -6r+3r=3-2r | | 4(2n+5)=3n+10 | | 5x-1x=20 | | 86.3+0.825= | | 64=16t^2+80t | | 130-8n^2=-1139 | | (3x+4)*(11x-6)=3x+4 | | 7=3B^2+2B^3 | | 3n+14=4n-7 |